Kepimpinan pengajaran di kalangan Pengetua dan hubungannya dengan komitmen guru - Indra Devi, Krishnan (2009)
Recent developments in the world of education and awareness of societies toward the critical role of school principals leadership and school effectiveness being the focus of a number of studies today. Therefore, the purpose of this study is to identify the relationship between instructional leadership among principals and teachers commitment towards organization. Each teacher surveyed responded to 59 questions from Principals' Instructional Leadership Questionaire and 17 questions from Teachers' Job Commitment Questionaire which were used to collect data. The usable data were collected from 350 secondary school teachers in Kuala Muda. T-test technique was used to determine the differentials in principals' instructional leadership behavior. Pearson Correlation technique was used to determine the strength of relationship between principals' leadership behavior with teachers' commitment. The results of this study shows that there are high levels of principals' instructional leadership in schools. They play significant roles in controlling teaching and learning in schools and encouraging efforts to increase profesionalisme among teachers. It was also found that there is significant correlation between principals' instructional leadership behavior with teachers' job commitment